# how to transform the equation? $\frac{\partial L(m,\lambda)}{\partial m}=2 \cdot \Sigma m+ \lambda \cdot \mathbf{1}$ [closed]

How to transform the equation $\frac{\partial L(m,\lambda)}{\partial m}=2 \cdot \Sigma m+ \lambda \cdot \mathbf{1}$ into $m=-\frac{1}{2} \cdot \lambda \Sigma^{-1} \mathbf{1}$, where $\mathbf{1} = \left( \begin{matrix} 1 \\ 1 \\ 1 \end{matrix}\ \right), m=(m_a,m_b,m_c), \Sigma$ is a $3 \times 3$ matrix, $\lambda$ is a scalar?

## closed as unclear what you're asking by BLAZE, Servaes, SchrodingersCat, Crostul, user223391 Nov 29 '15 at 5:20

Please clarify your specific problem or add additional details to highlight exactly what you need. As it's currently written, it’s hard to tell exactly what you're asking. See the How to Ask page for help clarifying this question. If this question can be reworded to fit the rules in the help center, please edit the question.

## 1 Answer

This holds if and only if $\frac{\partial L}{\partial m} = 0$. In this case, you obtain the equation $$0 = 2\cdot\Sigma m + \lambda\cdot \mathbf{1},$$ which is equivalent with your expression for $m$ after shuffeling some terms around.